1996
DOI: 10.1071/mf9960211
|View full text |Cite
|
Sign up to set email alerts
|

Testing protein-walled microcapsules for the rearing of first-feeding gilthead sea bream (Sparus aurata L.) Larvae

Abstract: Two basic types of protein-walled microcapsules were developed with the aid of using different preparation techniques. One type (Type A) was spherical and hard-walled, whereas the other (Type G) was irregularly shaped and soft-walled. The present work examined the larval growth and development of Sparus aurata reared either with these microcapsules as the sole food source or with a mixed diet of microcapsules and rotifers from the start of feeding. Larvae fed on Type A microcapsules evacuated them practically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 15 publications
1
26
0
1
Order By: Relevance
“…Ali 24 reported that juvenile Penaeus indicus, fed on ovalbumin feeds, discarded higher amounts of faecal nitrogen. Similar results were reported in larvae of the marine fish, Sparus aurata, fed with ovalbumin-based feed that inhibited the digestive proteinases, 25 and yielded lower growth and survival of the larvae. 26 The kinetics of inhibition of shrimp proteinases using MC 1 and MC 2 was obtained and results shown in Fig.…”
Section: Inhibition Of Proteinases By Feedstuffssupporting
confidence: 74%
“…Ali 24 reported that juvenile Penaeus indicus, fed on ovalbumin feeds, discarded higher amounts of faecal nitrogen. Similar results were reported in larvae of the marine fish, Sparus aurata, fed with ovalbumin-based feed that inhibited the digestive proteinases, 25 and yielded lower growth and survival of the larvae. 26 The kinetics of inhibition of shrimp proteinases using MC 1 and MC 2 was obtained and results shown in Fig.…”
Section: Inhibition Of Proteinases By Feedstuffssupporting
confidence: 74%
“…A presença de maior quantidade de reserva no fígado e vacuolização do intestino, mesmo após a transição alimentar aos cinco dias, sugere que, mesmo com uma ligeira redução no peso, as larvas do tratamento AV5DMP podem ter recebido maior aporte de nutrientes, como resultado dos efeitos da suplementação enzimática. A presença de vacúolos nos enterócitos e nos hepatócitos caracteriza a ocorrência de absorção de nutrientes (Yúfera et al, 1996), que refletiu nos resultados de crescimento, visto que as larvas do tratamento AV5DMP apresentaram peso maior (Tabela 2) que o das alimentadas com a dieta sem enzimas exógenas.…”
Section: Resultsunclassified
“…Changes in energy content during larval development in J mg )1 dry matter (s) and J mg )1 ash-free dry matter(h) (FF first feeding; M start of metamorphosis) (from Yu´fera et al, 1999). (Yu´fera et al, 1996;Ferna´ndez-Dı´az and Yu´fera, 1997), may contribute to improve reproducibility of weaning success of S. senegalensis on an industrial scale. Furthermore, the molecular form of the dietary amino acids, in particular the relative proportion in which different types of free amino acids (FAA), small peptides and proteins are present in the diet, may be important for growth.…”
Section: Weaningmentioning
confidence: 99%